Robust structural control of a real high-rise tower equipped with a hybrid mass damper - Koutsoloukas, Lefteris; Nikitas, Nikolaos; Aristidou, Petros (My University, 2022)
In this paper, the robust control of a real high-rise tower is studied, using a newly proposed, in the structural control field, Robust Model Predictive Control scheme (RMPC). Two RMPC controllers were designed considering either displacement mitigation (RMPC1) or power consumption efficiency (RMPC2). The two controllers were compared to the benchmark, robustness-wise, H∞ control scheme to demonstrate their relative performance. A number of stiffness and damping uncertainty scenarios were designed based on a broad study of the relevant literature, in order to estimate the robustness of each of the three controllers. In all scenarios, variable actuator uncertainty of (Formula presented.) was introduced. It was found that all controllers are effective in controlling the tower and demonstrate robustness against parametric and actuator uncertainties with different relative merits over each other. Indicatively, when considering root-mean-square (RMS) and peak displacement and acceleration reduction, the H∞ had an average performance reduction of 24%, the RMPC1 31% and the RMPC2 28% against their uncontrolled equivalent.
Keywords: Actuator uncertainty; Parametric uncertainty; Robust controller; Robust Model Predictive Control; Structural control; Tall Buildings; Tuned mass damper